Sustainable Energy Transition in Remote Islands: Evaluating Wind–Solar Hybrid Systems to Support Commercial Green Tourism on Kei Kecil Island - Saika Khoolish Rochma Fa’alih; Muhammad Rafif Dzaky Abdad; Novita Vadina Marta Ria; Wildan Yusril Nurhuda Rizkiawan; Yuki Trisnoaji (Universitas Negeri Jakarta, 2026)
This study aims to analyze the techno-economic feasibility of a hybrid microgrid system designed to support commercial green tourism infrastructure on Kei Kecil Island, Southeast Maluku. The research focuses on evaluating the investment feasibility of adding a 99 kW wind power plant to an existing system comprising photovoltaic (PV), diesel generators, and batteries. The methodology employs HOMER Pro simulation to assess key financial indicators and environmental impacts, with a particular emphasis on carbon emission reduction. Simulation results indicate that the proposed hybrid scenario offers a highly profitable investment strategy, characterized by a high return on investment (ROI) and a rapid payback period of under five years. These findings confirm that integrating wind energy not only significantly increases the renewable energy fraction but also suppresses the cost of energy to a competitive level compared to conventional generation. The novelty of this study lies in the specific analysis of wind turbine intervention on a brownfield architecture in a remote island setting, distinguishing it from typical greenfield design studies. This research provides a significant contribution to policymakers and investors as a validation model for energy transition supporting sustainable tourism in archipelagic regions.